Análise de SNPs do DNA mitocondrial em indivíduos residentes no estado do Espírito Santo para aplicação na Identificação Humana - Ambrosio, Isabela Brunelli [UNESP] (2015)
Human identification through DNA is one of the most revolutionary products of Modern Genetics, making it an indispensable tool in criminal investigation. This identification is based on the genetic profile of the individual, the combination of several markers inherited from their parents. The markers are generally differences in nuclear and DNA sequences between individuals (polymorphisms). In some cases, the analysis of nuclear DNA cannot be applied, the most successful alternative is the analysis of mitochondrial DNA (mtDNA). Mitochondria are intracellular organelles with a double membrane present on all nucleated mammalian cells with separate and distinct extrachromosomal genome nuclear genome, the mt DNA. Most laboratories use typing based mtDNA polymorphisms in the nucleotide sequence in the noncoding region (also known as the control region, the hypervariable or D-loop) of mtDNA. However, in some haplogrupos classification may not be possible based on only control data region. Thus, studies suggest the need for additional typing single nucleotide polymorphisms (SNPs) in other regions of mtDNA, especially in cases where it is not possible to differentiate individuals only by the analysis of hypervariable region. This study aimed to analyze, analyze thirty (30) SNPs of mtDNA in samples of unrelated individuals born and living in the State of Espírito Santo, allowing their classification in haplogroups and complementing the SNPs data of mtDNA control region achieved in previous work in the laboratory, for later use in forensic cases. A total of 100 samples, 19 were found haplogroups and the sample were classified according to its origin: 43% African, 30% European, 26% Native American, and 1% Asian. The haplogroup was found more L3 having African origin. Some samples of previous work could not be correctly classified only with the sequencing of the control region of mtDNA, after analysis of 30...